Study on flow field characteristics of bulk grain transport based on CST blade swirling device - Hanshan Zhang; Yongxiang Li; Xuemeng Xu; Wenji Wei; Haihao Song; Kun Shang (Cogent Food & Agriculture)
To address wheat particle settling during pneumatic conveying, blade aerodynamics were optimized to minimize friction and improve efficiency. Using the CST parameterization method, blade airfoil contours were generated and optimized via nonlinear sequential quadratic programming to maximize suction angle and lift coefficient. Based on this, multi-stage spinning devices with 3, 5, and 10 blades were designed. Numerical simulations using the SIMPLE algorithm analyzed axial/tangential velocities and static pressure drops. Results showed the 5-blade configuration achieved optimal performance: axial velocity increased by 25%/16.67%, tangential velocity by 37.5%/0%, and pressure drop reduced by 42.85%/82.857% compared to 3/10-blade systems. Experimental validation confirmed theoretical findings, demonstrating enhanced particle swirling without flow separation. This design effectively reduces wall friction, stabilizes particle trajectories, and improves conveying efficiency through optimized aerodynamic forces.